2003
DOI: 10.1128/jvi.77.15.8336-8344.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Cytomegalovirus DNA Polymerase by C-Terminal Peptides from the UL54 Subunit

Abstract: In common with other herpesviruses, the human cytomegalovirus (HCMV) DNA polymerase contains a catalytic subunit (Pol or UL54) and an accessory protein (UL44) that is thought to increase the processivity of the enzyme. The observation that antisense inhibition of UL44 synthesis in HCMV-infected cells strongly inhibits viral DNA replication, together with the structural similarity predicted for the herpesvirus processivity subunits, highlights the importance of the accessory protein for virus growth and raises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 51 publications
2
79
0
Order By: Relevance
“…Thus, this UL54 peptide is less ␣-helical than the analogous peptide derived from the HSV catalytic subunit, UL30 (16). This observation is consistent with circular dichroism studies demonstrating that the C-terminal peptide of HCMV UL54 is less ␣-helical in solution than similar peptides from HSV UL30 (29,30). The UL54 peptide makes several interactions with regions on the front face of UL44, which are detailed below.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Thus, this UL54 peptide is less ␣-helical than the analogous peptide derived from the HSV catalytic subunit, UL30 (16). This observation is consistent with circular dichroism studies demonstrating that the C-terminal peptide of HCMV UL54 is less ␣-helical in solution than similar peptides from HSV UL30 (29,30). The UL54 peptide makes several interactions with regions on the front face of UL44, which are detailed below.…”
Section: Resultssupporting
confidence: 72%
“…The interaction between UL44 and UL54 would make an attractive drug target because it is specific and differs in important details from the PCNA-binding partner interactions and because both proteins are essential for viral replication (3,4,55). The interaction is known to be inhibited by peptides corresponding to the C-terminal 22 residues of UL54 (29), and the interaction has been shown to be sensitive to amino acid substitutions in either of the two subunits (12,19). A similar strategy has been utilized for their counterparts in HSV (30,31,56), and small molecules have been identified that block both the HSV UL42-UL30 interaction in vitro and viral replication (57).…”
Section: P21mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that a peptide corresponding to the C-terminal 22 residues of UL54 could both disrupt the physical interaction between UL54 and UL44 and specifically inhibit the stimulation of UL54 activity by the accessory protein (17). These findings suggested, but did not demonstrate, that UL54 interacts via its extreme C terminus with UL44.…”
mentioning
confidence: 60%
“…The observations that both UL54 and UL44 are essential for HCMV DNA replication (21)(22)(23) and that the UL54-UL44 interaction is specific (17) make this interaction an attractive drug target. Recently, it was reported that a peptide corresponding to the C-terminal 22 residues of UL54 could both disrupt the physical interaction between UL54 and UL44 and specifically inhibit the stimulation of UL54 activity by the accessory protein (17).…”
mentioning
confidence: 99%